Darma: Defeating and reconnaissance manna-karma attacks in 802.11 with multiple detections and prevention - Baharudin, Norzaidi; Mohd Ali, Fakariah Hani; Naim @ Mohayat, Mohd Hariz (World Academy of Research in Science and Engineering, 2020)
The vast growing usage of mobile phones increases Wi-Fi technology. At present, the pattern of human interaction with the internet is not a desktop or laptop anymore. The assimilation of tools for surfing, working, and communication is now shifting to mobile phones. Thus, this is the motivation to expand Wi-Fi technology so that it will be the primary medium for internet connectivity. Hence, increasing the security risk for it attracts attackers despite its popularity among users. The DOS attack in 802.11 management frames is widely known as an initial process before Man-in-the-middle (MiTM) attacks in 802.11 takes part. Karma and Manna's attacks are an unprecedented attack in the 802.11 management frames. This paper proposed a mechanism called Defeating and Reconnaissance Manna-karma Attack (DARMA), which is client-side multiple detection techniques to defeat and prevent karma-manna attack. The proposed mechanism consisted of 4 layers of processes inclusive of monitors, detection, confirmation, and preventions. The effectiveness of the detection is base of the current real-time behaviour of the packets.